Uniform whole body immobilization device for radiotherapy - Anshor, Nugroho; Listyawan, Syahara; Boedi H, Heroe; Setyo N, Dwi (Faculty of Medicine, 2026)
Radiotherapy is a treatment modality that utilizes radiation, either from radioactive sources or generated by a Linear Accelerator (Linac). To ensure precise targeting and protect surrounding healthy organs, accurate and stable patient immobilization is essential. Immobilization devices vary by treatment area—such as the head, head and neck, thorax, and pelvis—but are typically limited to one unit per type, posing challenges when treating multiple patients with similar conditions simultaneously. This study aims to evaluate the accuracy of a newly developed immobilization tool called UNIMOB (Uniform Whole Body Immobilization Device), designed as an affordable and flexible alternative.